2003
DOI: 10.1046/j.1444-2906.2003.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Activities of mesencephalic nucleus neurons during fictive swimming of the carp Cyprinus carpio

Abstract: Fish swim by undulatory contractions of the axial trunk musculature. It has been presumed that a descending signal from the brainstem activates central pattern generators in the spinal cord to make the swimming rhythm. In the carp the electrical or chemical stimulation of a mesencephalic nucleus, the nucleus fasciculi longitudinalis medialis (Nflm), could initiate swimming. However, it has not been established what signals originate from the Nflm in order to make the fish swim. The activity of the Nflm neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The firing frequency of one subtype increased linearly in proportion to the tail-beat frequency, whereas the firing frequency remained constant in the other subtype. Similar results have been obtained in immobilized carp [Baba et al, 2003]. We also observed that electrical destruction of our tracer injections into the Nflm led to immobilization or abnormal swimming [Uematsu et al, unpublished].…”
Section: Activities Of Nflm Neurons During Fish Swimmingsupporting
confidence: 75%
“…The firing frequency of one subtype increased linearly in proportion to the tail-beat frequency, whereas the firing frequency remained constant in the other subtype. Similar results have been obtained in immobilized carp [Baba et al, 2003]. We also observed that electrical destruction of our tracer injections into the Nflm led to immobilization or abnormal swimming [Uematsu et al, unpublished].…”
Section: Activities Of Nflm Neurons During Fish Swimmingsupporting
confidence: 75%
“…Although chronic recordings of single or multi unit activities from the central nervous system have been well examined in some mammals including cats 1 and rats, 2,3 this approach for revealing neural mechanisms underlying behaviors are scarce in fish. In investigating the mechanisms of the central nervous system during teleost locomotion, monitoring of fictive swimming in immobilized preparations has been mainly used 10–12 . However, in these experiments, technical difficulties and surgical damage to the subjects were large problems 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The roles of the cerebellum include fine control of body movement, 7–9 and hence it is suitable for the present purpose in that it involves observation of neural correlations of motor activities. It is difficult to monitor the fine coordination of behavior, such as organized fin movements during turning, in conventional restricted conditions including fictive locomotor activity 10–12 . Chronic recording of the neural activities from unrestrained preparations has considerable advantages to reveal fine motor control by the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…Brain lesion, electrophysiological, and electrical stimulation studies indicate that this nucleus is involved in swimming through the control of trunk and tail muscles (Uematsu & Todo ; Baba et al . ; Kobayashi et al . ).…”
Section: Descending Pathways From Mesencephalonmentioning
confidence: 99%
“…This nucleus sends fibers throughout the length of the spinal cord (Bosch & Roberts 2001), although the exact sites of terminations within the spinal grey remain unclear. Brain lesion, electrophysiological, and electrical stimulation studies indicate that this nucleus is involved in swimming through the control of trunk and tail muscles (Uematsu & Todo 1997;Baba et al 2003;Kobayashi et al 2009). A thorough knowledge on the afferent and efferent connections of the nucleus of medial longitudinal fascicle would help determine if the nucleus serves similar roles as those of the interstitial nucleus of Cajal of mammals.…”
Section: Descending Pathways From Mesencephalonmentioning
confidence: 99%